Research on Theme Creation and the Path of "Sinicization of Oil Painting" in Contemporary Realistic Oil Painting in China (Journal of Global Arts Studies, 2025)
Background： Rooted in social and humanistic concerns, Chinese realism has evolved under Western and indigenous influences, highlighting a shift toward thematic creation and Sinicization amid cultural transformation. Objective： This paper aims to explore the developmental path and expressive characteristics of contemporary Chinese realistic oil painting in the context of thematic creation and the Sinicization process, revealing its cultural foundations and potential future directions. Methods: By tracing the historical context of art development and examining the evolution of ideological concepts, visual language, and thematic construction, this study analyzes representative artists and works from both theoretical and practical perspectives. Results: Thematic creation strengthens realism’s narrative and social depth, while Sinicization localizes its aesthetics and culture, shaping a distinctive artistic language of its time. Conclusion: The development of contemporary Chinese realism addresses social and cultural needs while reflecting artistic innovation and cultural awareness, offering insights into the future of realism and its Sinicization.
Keywords: Realistic Oil Painting; Thematic Creation; Sinicization of Oil Painting; Artistic Development